Finerenone and effects on mortality in chronic kidney disease and type 2 diabetes: a FIDELITY analysis. Issue 2 (13th January 2023) - Filippatos, Gerasimos; Anker, Stefan D; August, Phyllis; Coats, Andrew J S; Januzzi, James L; Mankovsky, Boris; Rossing, Peter; Ruilope, Luis M; Pitt, Bertram; Sarafidis, Pantelis; Teerlink, John R; Kapelios, Chris J; et al.
Abstract: Aims: Finerenone reduces the risk of cardiovascular events in patients with chronic kidney disease (CKD) and type 2 diabetes (T2D). We investigated the causes of mortality in the FIDELITY population. Methods and results: The FIDELITY prespecified pooled data analysis from FIDELIO-DKD and FIGARO-DKD excluded patients with heart failure and reduced ejection fraction. Outcomes included intention-to-treat and prespecified on-treatment analyses of the risk of all-cause and cardiovascular mortality. Of 13 026 patients [mean age, 64.8 years; mean estimated glomerular filtration rate (eGFR), 57.6 mL/min/1.73 m 2 ], 99.8% were on renin–angiotensin system inhibitors. Finerenone reduced the incidence of all-cause and cardiovascular mortality vs. placebo (8.5% vs. 9.4% and 4.9% vs. 5.6%, respectively) and demonstrated significant on-treatment reductions [hazard ratio (HR), 0.82; 95% confidence interval (CI), 0.70–0.96; P = 0.014 and HR, 0.82; 95% CI, 0.67–0.99; P = 0.040, respectively]. Cardiovascular-related mortality was most common, and finerenone lowered the incidence of sudden cardiac death vs. placebo [1.3% (incidence rate 0.44/100 patient-years) vs. 1.8% (0.58/100 patient-years), respectively; HR, 0.75; 95% CI, 0.57–0.996; P = 0.046]. The effects of finerenone on mortality were similar across all Kidney Disease: Improving Global Outcomes risk groups. Event probability with finerenone at 4 years was consistent irrespective of baseline urine albumin-to-creatinine ratio, but seemingly more pronounced in patients with higher baseline eGFR. Conclusion: In FIDELITY, finerenone significantly reduced the risk of all-cause and cardiovascular mortality vs. placebo in patients with T2D across a broad spectrum of CKD stages while on treatment, as well as sudden cardiac death in the intention-to-treat population. Clinical trials registration: FIDELIO-DKD and FIGARO-DKD are registered with ClinicalTrials.gov, numbers NCT02540993 and NCT02545049, respectively (funded by Bayer AG). Graphical Abstract: